BIMBINGAN KEAGAMAAN TENTANG ASWAJA AN-NAHDLIYAH PADA KELOMPOK KEGIATAN DZIKIR FIDA’ PUTRI DI MASJID AL- AMIN DESA SOKO, BANDUNG, TULUNGAGUNG - Fatik Lutviana Anggraini; Vera Feryyal (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2021)
Religious issues brought up by a number of Islamic groups in Indonesia often lead to bad understanding in the community because they contain provocations and attempts to corner these Islamic groups. This service aims to respond to and counteract the deviant ideological understanding that is why this activity is important to be encouraged in the midst of society. The method of service is coordination, communication, implementation of activities and evaluation. The location of the service is in Soko Village, Bandung, Tulungagung Regency. The target of the service is the Dhikr Fida' Putri Activity Group at the Al-Amin Mosque, Soko Village, Bandung, Tulungagung. The results of the service activities include: a) Service activities have a positive impact on residents at the service location, namely reviving a religious atmosphere, instilling an attitude of togetherness, uniting the local community.